2018
DOI: 10.25135/rnp.21.17.07.118
|View full text |Cite
|
Sign up to set email alerts
|

New Cytotoxic Pregnane-type Steroid from the Stem Bark of Aglaia elliptica (Meliaceae)

Abstract: A new pregnane-type steroid, 2α-hydroxy-3α-methoxy-5α-pregnane (1), together with three known dammarane-type triterpenoid, 3β-acetyl-20S,24S-epoxy-25-hydroxydammarane (2), 20S,24S-epoxy-3α,25-dihydroxydammarane (3), and eichlerianic acid (4) have been isolated from the stem bark of Aglaia elliptica. The structures were determined by spectroscopic methods including the 2D-NMR techniques. Compound 1-4 showed moderate cytotoxic activity against P-388 murine leukemia cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…These functionalities accounted as four out of the total nine indices of hydrogen deficiency. The remaining five indices of hydrogen deficiency were consistent to the pregranetype steroidal skeleton with a tigloyl amino group, N-methylaminoethane substituent and additional an epoxide ring (Kaulanai et al, 2002;Farabi et al, 2018;Wu et al, 2019). To clarify the position of functional group in 1, 2D NMR experiments were carried out and the results as shown in Figure 2.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…These functionalities accounted as four out of the total nine indices of hydrogen deficiency. The remaining five indices of hydrogen deficiency were consistent to the pregranetype steroidal skeleton with a tigloyl amino group, N-methylaminoethane substituent and additional an epoxide ring (Kaulanai et al, 2002;Farabi et al, 2018;Wu et al, 2019). To clarify the position of functional group in 1, 2D NMR experiments were carried out and the results as shown in Figure 2.…”
Section: Discussionmentioning
confidence: 80%
“…A methine proton at  H 2.51 was mutually coupled to methyl at  H 1.12 and were correlated to oxygenated carbon at C-17 ( C 72.9), indicated N-methylaminoethane substituent was attached at C-17. The relative stereochemistry of 1 was determined on the basis of coupling constant in the 1 H-NMR spectrum and a biogenetic point of view the occurrence of pregnanetype steroidal structure in natural (Rahman et al, 2002;Farabi et al, 2018). These observations along with the similarity of spectral data and physicochemical properties between 1 and previously reported (20S)-20-(N-methylamino)-3-(tigloyl-amino)-5-pregnan-16,17-epoxy-4-one, isolated from the leaves Sarcococca coriacea (Kaulani et al, 2002;Wu et al, 2019), let us identify 1 as (20S)-20-(N-methylamino)-3-(tigloyl-amino)-5-pregnan-16,17-epoxy-4-one, which isolated from marine sponge Xestospongia sp for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…The further chemical investigation on this species gave six new limonoid compounds, i.e. munronins A-F (21)(22)(23)(24)(25)(26). In compounds 23-26, the side chains were relatively rare in limonoid compounds, which is α,βunsaturated lactone, α,β-unsaturated lactam, and alkyne groups, respectively [57].…”
Section: Limonoidmentioning
confidence: 97%
“…Meliaceae is well known as a source of diverse natural compounds with interesting biological activity. Some compounds including sesquiterpenoids [2][3][4][5][6][7], triterpenoids [8][9][10][11][12][13][14][15][16][17][18], diterpenoids [19][20][21], steroids [22][23][24][25], limonoids [26][27], alkaloids [28][29], lignan [30][31][32], flavaglines [33][34][35], and flavonoids [36][37] have been successively extracted from this family. Those isolated compounds showed interesting biological activities including cytotoxic [38][39][40][41], insecticidal [42][43], antimycobacterial [6], antifungal [44][45], antiinflammatory [9,[46]…”
Section: ■ Introductionmentioning
confidence: 99%
“…The cytotoxicity effects of the two isolated compounds (1 and 2) against the P-388 murine leukemia cells were conducted according to the method described in previous paper (Harneti et al, 2012;Harneti et al, 2014;Farabi et al, 2017) and were used an Artonin E (IC 50 0.75 µg/mL) as a positive control (Farabi et al, 2018;Hidayat et al, 2017). Cytotoxic activity of two dammaranetype triterpenoids, 3α-asetil-20S,24S-epoxy-25-hydroxydammarane (2) showed stronger activity than 20S,24S-epoxy-25hydroxydammarane (1), indicated that the presence of an acetyl group increase the cytotoxic activity in dammarane-type triterpenoid sctructure.…”
Section: α-Acetyl-20s24s-epoxy-3α25dihydroxydammarane (2)mentioning
confidence: 99%